Electronic Textile Sensors for Decoding Vital Body Signals: State‐of‐the‐Art Review on Characterizations and Recommendations. (12th January 2022) - Shuvo, Ikra Iftekhar; Shah, Aastha; Dagdeviren, Canan
Abstract : The digitization of textiles (textronics) has created new opportunities for integration with conformable sensors to enable unobtrusive, noninvasive, and continuous decoding of vital body signals. This article provides an in‐depth review of the materials and fabrication methodologies used for textronic sensors per their form‐factor in the textile manufacturing process chain—fiber, yarn, fabric, and apparel. Next, it analyzes the performance characterization techniques currently used for these sensors and highlights the needs for standardized test methods in the following aspects: biocompatibility, thermal and tactile comfort, aging, and operation of the biomedical sensing modality at standard human stretch. It also identifies the significance of pretreatment and conditioning reporting of the textile form‐factors based on their impact on mechanical and electric performance of the textronic sensor. The study concludes by recommending a universal testing roadmap for textronic sensors which is expected to veritably complement the work of different standardization committees, including CEN TC‐248/WG‐31, IEC TC‐124, ASTM D13.50, and AATCC RA111. Abstract : The inherent conformability and diverse form‐factors of textile electronics allow efficient and unobtrusive monitoring of biosignals from curvilinear body surfaces. While a variety of sensors have been developed, there is a definitive need for a universal framework within which to understand and characterize device performance (both as textiles and as medical sensors) and streamline its quality control and testing standards.